Estado del arte del proceso de deshidrogenación del propano para la producción de propileno - Castro Serrano, Malcon Martín (Ingenierias, 2017)
Propylene is one of the most important petrochemical products worldwide, experiencing an annual growth of 5.7% in its demand over the last two decades. The propane dehydrogenation is one of the most used synthesis routes and therefore been subject of several research studies, aimed to overcome the kinetic limitations of the reactions that take place during the process. The influence of the catalyst has been studied by testing different types of catalysts or modified versions of these. Additionally, comparisons have been made among the existing processes for propylene production, emphasizing the type of reactor used and observing the increase in efficiency as a function of its geometry. New investigations on the use of membranes are covered, in order to favor the hydrogen absorption and achieve favorable conditions for the operating variables. As a result of this study, it is observed that the modifications in the content of metals in the catalysts, as well as in the structure of the supports of these, provide excellent benefits in the performance of the process. The same happens with the different configurations of the reactors in order to favor of the operating conditions